Hubungan Antara Pengetahuan dan Tingkat Pendidikan Petugas Pengelola Obat dengan Ketepatan Waktu Penyerahan Lembar Permintaan dan Laporan Penggunaan Obat (LPLPO) Pada Puskesmas di Kabupaten Bengkulu Utara - Dwi Hermawati (Peneliti.net, 2022)
Pursuant to LPLPO Puskesmas which step into part of Pharmacy and Perbekes per month ( timely report enter the date of 1 - 5 per month) still be found by the existence of puskesmas which mistime in giving report. In the year 2007 from 25 puskesmas [of] exist in Bengkulu North only 30 % what timely LPLPO, in the year 2008 from 25 puskesmas [of] exist in Bengkulu North only 35 % what timely LPLPO ( Source ; Rekapan of Report of LPLPO Monthly Mount the Puskesmas year 2007 - 2008). this Delay LPLPO [is] very influencing from [at] record-keeping and reporting of exist in shares of Pharmacy and Perbekes of Public Health Service of Bengkulu North, among other things the forwarding of supply report medicinize from regency to province will be lost time, making of rekapan of monthly report require the time old ones and more important again for puskesmas at the (time) of intake schedule medicinize for the report of overdue, drug required [by] its amount sometimes disagree with request raised. Because available drug is beforehand distributed to correct puskesmas of time in forwarding of LPLPO. ( Depkes RI, 2004:35). In this research, sampel taken to be [done/conducted] Totally is Sampling that is where researcher [do/conduct] the survey to entire/all source population ( Murti, 2006:85 , hence in this research [is] sampel taken by all organizer worker medicinize at 19 puskesmas of Regency of Bengkulu North as much 38 people. All result of research data is beforehand presented through tables of distribution frekuensi.Kemudian analyse the data conducted step by step from analysis of univariat and bivariate, that is test the Chi-Square constructively software program. Result of research indicate that there [is] [relation/link] having a meaning between storey;level of responder knowledge with the accuracy of time of delivery of LPLPO mount puskesmas [in] Regency of Bengkulu North.